2022
DOI: 10.1038/s41598-022-09747-z
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian network meta-analysis of face masks' impact on human physiology

Abstract: Several concerns regarding the safety of face masks use have been propounded in public opinion. The objective of this review is to examine if these concerns find support in the literature by providing a comprehensive overview of physiological responses to the use of face masks. We have performed a systematic review, pairwise and network meta-analyses to investigate physiological responses to the use of face masks. The study has been registered with PROSPERO (C RD42020224791). Obtained results were screened usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Furthermore, this recent scoping review on mask driven adverse effects and health risks has summoned for a systematic review. Though some important systematic reviews regarding masks and their effects already exist [21][22][23][24] , they are predominantly restricted to healthy and sportive individuals 21,23 . Due to the exclusion of children, pregnant women and diseased patients from these evaluations and conclusions 22,25 , the reviews do not provide sufficient evidence that masks can be employed in the general population as safe protective measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this recent scoping review on mask driven adverse effects and health risks has summoned for a systematic review. Though some important systematic reviews regarding masks and their effects already exist [21][22][23][24] , they are predominantly restricted to healthy and sportive individuals 21,23 . Due to the exclusion of children, pregnant women and diseased patients from these evaluations and conclusions 22,25 , the reviews do not provide sufficient evidence that masks can be employed in the general population as safe protective measures.…”
Section: Introductionmentioning
confidence: 99%
“…Though some important systematic reviews regarding masks and their effects already exist [21][22][23][24] , they are predominantly restricted to healthy and sportive individuals 21,23 . Due to the exclusion of children, pregnant women and diseased patients from these evaluations and conclusions 22,25 , the reviews do not provide sufficient evidence that masks can be employed in the general population as safe protective measures. Moreover, the application of fixed statistical models 21 , use of narratives rather than quantitative analysis and statistics (despite claiming to be systematic) 26 , focus only on health care workers and their complaints 25 , as well as comparing the different mask types without any baseline/control group 25 were ubiquitous limitations of those studies.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the mask did not alter heart rate, saturation, and distance, while dyspnea variations were clinically significant. Physiological variations when using face masks whilst performing low-intensity physical activity were found to be reduced when wearing a surgical mask with respect to an N95 mask, as shown by Litwinowicz et al [ 13 ].…”
Section: Introductionmentioning
confidence: 93%
“…Further than the effects on vocal production are concerned, the use of face masks also affects physiological parameters, as shown in a recent review by Litwinowicz et al [ 13 ]. Even though some works have shown that heat stress is a significant concern when wearing a face mask, regardless of the performed activity, poor information is available about the effect of a face mask during amatorial or professional sports practice.…”
Section: Introductionmentioning
confidence: 99%
“…The recommended mask to wear for exercising is a comfortable mask, not too tight, but still able to prevent the spread of the virus [7]. However, previous studies have shown that wearing a surgical facemask or even a N95 filtering facepiece during exercising at low-tomoderate work rate has no physiological impact [5], [6], [8]. Thus, an experiment was conducted, in this study, to analyze physiological ergonomics aspect, whether people wearing different type of masks during physical activities and distraction of music would affect heart rate.…”
Section: Introductionmentioning
confidence: 99%